Symbolic Meaning Momeati Ritual Preserving Gorontalo Cultural Identity: Makna Simbolik Ritual Momeati Melestarikan Identitas Budaya Gorontalo - Nurullana A. Pala; Syamsuddin Syamsuddin; Fadillah Fadillah; Yunidar Yunidar; Nirmayanti Nirmayanti (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Indonesia possesses diverse local cultures and traditions that require consistent preservation to maintain a robust national character. Specific Background The Mome’ati ceremony serves as a crucial life-cycle custom marking a young girl's transition to adulthood through complex verbal and nonverbal representations. Knowledge Gap Rapid modernization precipitates a shift in understanding these traditional elements among the younger generation, risking the gradual loss of profound philosophical, moral, and religious dimensions. Aims This study analyzes the semiotic elements within the ceremonial procession to ensure local heritage preservation and intergenerational comprehension. Results Utilizing a qualitative anthropological approach and semiotic frameworks by Peirce and Fiske, the findings demonstrate that the ritual's five stages contain distinct elements—such as white clothing, candles, betel nut, and ceremonial poetry—that represent purity, social responsibility, harmony, and spiritual commitment. Novelty This research uniquely categorizes the verbal prayers and nonverbal artifacts as an integrated ideological communication system that harmonizes Islamic tenets with indigenous philosophies. Implications Sustaining this heritage necessitates active transmission by families, customary institutions, and educational bodies to ensure fundamental ethical values remain relevant in contemporary society. Highlights Semiotic analysis reveals profound religious and moral values within traditional ceremonial transitions. Verbal prayers and nonverbal artifacts function as an integrated ideological communication system. Modernization necessitates active intergenerational transmission to sustain indigenous philosophies among youths. Keywords Semiotic Analysis; Indigenous Ceremonies; Moral Education; Intergenerational Transmission; Anthropological Linguistics